= <span>6x + 2(3x + 5) + (-9)
= 6x +6x + 10 - 9
= 12x + 1
In short, Your Final Answer would be 12x + 1
Hope this helps!</span>
Answer:
2x + 1 = 15
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
hope this helps but I'm not sure if it's right sorry if wrong
Answer:
D
Step-by-step explanation:
Given
6x² - 2x + 36 = 5x² + 10x ( subtract 5x² + 10x from both sides )
x² - 12x + 36 = 0 ← in standard form
(x - 6)² = 0 ← in factored form, thus
x - 6 = 0 ⇒ x = 6 → D
Answer:
Height of second tower = 17.32m
Step-by-step explanation:
I have attached a diagram depicting the question.
From the diagram, The first tower is depicted by side AEB and the second tower CD.
While d is the distance that separates the two towers and it's given as 15m.
Now, since the angle of depression of the second tower’s base is 60°, then for triangle BAC. Angle C = 60°.
Thus; using trigonometric ratios;
tan 60° = AB/AC.
This gives; AB = d*tan 60°
Similarly, for the triangle BED, BE = d*tan 30°
Since, AE = CD, thus ;
CD = AB − BE
CD = d (tan 60° − tan 30°)
CD = 15(1.7321 − 0.5774)
CD = 15 × 1.1547
CD ≈ 17.32 m.
So, height of second tower = 17.32 m